Reflection in university and the employability agenda: a discourse analysis case study. Issue 4 (4th July 2017) - Wharton, Sue
Abstract: In UK universities, reflection is promoted not only for its intrinsic value but also for instrumental purposes, for students to gain and demonstrate skills and attributes which are valued by employers. In this paper, I examine reflective writing produced by students seeking an award offered by the careers department of one university. By looking at the evaluative language choices made by the student writers, I shed light on some of their practices regarding self-representation and their articulations of experience. I provide a critical account of what reflective writing looks like in this particular setting, and interpret this in the broader context of the goal to foster reflection among higher education students. I argue that the reflective writing engendered by this particular context and task is different in key respects from the reflection which is commonly advocated as an element of personal, professional or academic development.